(untitled) (Journal of Nepal Geological Society, 2004)
The Quaternary basin fill of the Kathmandu valley contains discontinuous and heterogeneous layers of lacustrine and fluvial sediments. The available stratigraphic information derived mainly from 185 boreholes ranging in depth from 35 to 575 m was used to study the layer model of the Kathmandu basin. For this purpose, the entire basin till was grouped into three representative layers containing mainly fluvial deposits, lacustrine deposits, and the overlying fluvial and anthropogenic materials. The information from borehole logs was incorporated into the three layers, and a digital elevation model of their depth of contacts was generated. The model was compared with the bedrock depth to obtain the thickness of each layer. A liquefaction susceptibility map of the Kathmandu valley was generated using the above information of the representative layers as well as 328 shallow (<30 m) boreholes.